Da teoria verde ao ecofeminismo: mulheres na África Meridional frente às mudanças climáticas - Ellen Monielle do Vale Silva; Fernanda Caroline Alves Bezerra de Melo (e-cadernos ces)
Considering the female presence in Southern Africa in regards to climate change, this article aims to analyze the subject in light of green and ecofeminist theories. In such perspective, the authors apply a qualitative approach methodology based on empirical and bibliographic analysis. The result of this work revolves around the discussion concerning the demonstration of how the aforementioned theories contribute to the ways African women act in facing climate change in the Southern region of Africa. It results as a conclusion that the main obstacles faced by gender inequality in the socioeconomic sphere are intensified by environmental impacts in the region, making women the main affected group.